Study on hysteresis or nonlinearity properties of MN-ZN ferrites - Zhang, Yong Ping. (2009)
A great deal of information can be learned about the magnetic properties of a material by studying its hysteresis loop. A hysteresis loop shows the relationship between the induced magnetic flux density (B) and the magnetizing force (H). MnZn ferrite has the good characteristics of high resistivity, good quality at high frequency and good performance of soft magnetism. In this project we will study on hysteresis or nonlinearity properties of MnZn ferrites theoretically and experimentally and simulate the hysteresis effect in the transformer circuit.